2022
DOI: 10.1007/s10548-022-00911-2
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam Modulates EEG Microstates in Temporal Lobe Epilepsy

Abstract: To determine the effects of Levetiracetam (LEV) therapy using EEG microstates analysis in a population of newly diagnosed Temporal Lobe Epilepsy (TLE) patients. We hypothesized that the impact of LEV therapy on the electrical activity of the brain can be globally explored using EEG microstates. Twenty-seven patients with TLE were examined. We performed resting-state microstate EEG analysis and compared microstate metrics between the EEG performed at baseline (EEGpre) and after 3 months of LEV therapy (EEGpost)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Figure 1 displays the number of biomarkers within each class and category and associated overall risk‐of‐bias rating (domain risk‐of‐bias ratings are in Table S2). A 15th category, Microstates, was identified but excluded from this review as the study 39 was undergoing peer review. Detailed Concept results will be discussed after Population and Context search results.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 displays the number of biomarkers within each class and category and associated overall risk‐of‐bias rating (domain risk‐of‐bias ratings are in Table S2). A 15th category, Microstates, was identified but excluded from this review as the study 39 was undergoing peer review. Detailed Concept results will be discussed after Population and Context search results.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a previous study conducted in patients with temporal lobe epilepsy has shown that levetiracetam induces a reduction in Microstate B duration and occurrence. 41 Since levetiracetam is extremely efficacious in suppressing PPR 42 , 43 and considering our findings, it could be argued that the changes of Microstate B induced by levetiracetam might reflect the inhibition of the hyper-excitability of the visual system. If confirmed, Microstate B temporal metrics could therefore potentially serve as biomarkers to assess the efficacy of ASMs on PS.…”
Section: Discussionmentioning
confidence: 63%
“…Finally, the parameters of the microstate (i.e., duration, occurrence, contribution, and transition probability) were calculated. Duration indicates that each microstate maintains a stable average time length when it appears; occurrence represents the number of times each microstate appears per second; contribution describes the proportion of the total time of each microstate; and transition probability indicates the probability of converting from one microstate to another ( Croce et al, 2020 ; Ricci et al, 2022 ). …”
Section: Methodsmentioning
confidence: 99%